1973
DOI: 10.1139/v73-396
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of α-VPO5

Abstract: a-VPO, crystallizes in the tetragonal space group P4/n with a = 6.014(7) and c = 4.434(2) A. The structure, isotypic with that of a-VS05, was refined by full-matrix least-squares method to an R value of 0.089 using 239 independent reflections. The vanadium ion lies on a crystallographic four-fold axis, as does one of the oxygen atoms, and the P on a site of 4 symmetry. A second oxygen atom, as a result of disorder, occurs in two positions which are mirror reflected with respect to the ac plane. The structure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0
4

Year Published

1976
1976
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(63 citation statements)
references
References 3 publications
2
57
0
4
Order By: Relevance
“…Several different polymorph of the oxidized VOPO 4 have been reported in the literature: [5][6][7][8] ␣ I -VOPO 4 , ␣ II -VOPO 4 , ␤-VOPO 4 , ␥-VOPO 4 , ␦-VOPO 4 , ⑀-VOPO 4 , and -VOPO 4 . During thermal treatment at high temperature the consecutive transitions ␣ I → ␣ II → ␤-VOPO 4 or ␦ → ␥ → ␤-VOPO 4 have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Several different polymorph of the oxidized VOPO 4 have been reported in the literature: [5][6][7][8] ␣ I -VOPO 4 , ␣ II -VOPO 4 , ␤-VOPO 4 , ␥-VOPO 4 , ␦-VOPO 4 , ⑀-VOPO 4 , and -VOPO 4 . During thermal treatment at high temperature the consecutive transitions ␣ I → ␣ II → ␤-VOPO 4 or ␦ → ␥ → ␤-VOPO 4 have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…The data, corrected for Lorentz-polarization and absorption, were used together with the parameters of disordered ~-VPO5 (Jordan & Calvo, 1973)to refine the structure. Convergence of the least-squares refinement yielded an R of 0.12 with residual peaks in the difference Fourier map that indicated that the compound was non-stoichiometric.…”
mentioning
confidence: 99%
“…In Fig. 2 Li 2 VGeO 5 has a structure very similar to ␣-VOPO 4 [11,12]. The layered units are isostructural except that the two interlayer Li + ions charge compensate for the V(IV) in our title compound.…”
Section: Resultsmentioning
confidence: 79%